Xenotransplantation panel for the detection of infectious agents in pigs. (18th August 2018) - Hartline, Caroll B.; Conner, Ra'Shun L.; James, Scott H.; Potter, Jennifer; Gray, Edward; Estrada, Jose; Tector, Mathew; Tector, A. Joseph; Prichard, Mark N.
Abstract: Background: Recent advances in xenotransplantation have produced organs from pigs that are well tolerated in primate models because of genetic changes engineered to delete major antigens from donor animals. To ensure the safety of human transplant recipients, it will be essential to understand both the spectrum of infectious agents in donor pigs and their potential to be transmitted to immunocompromised transplant recipients. Equally important will be the development of new highly sensitive diagnostic methods for use in the detection of these agents in donor animals and for the monitoring of transplant recipients. Methods: Herein, we report the development of a panel of 30 quantitative polymerase chain reaction (qPCR) assays for infectious agents with the potential to be transmitted to the human host. The reproducibility, sensitivity and specificity of each assay were evaluated and were found to exhibit analytic sensitivity that was similar to that of quantitative assays used to perform viral load testing of human viruses in clinical laboratories. Results: This analytical approach was used to detect nucleic acids of infectious agents present in specimens from 9 sows and 22 piglets derived by caesarean section. The most commonly detected targets in adult animals were Mycoplasma species and two distinct herpesviruses, porcine lymphotrophic herpesvirus 2 and 3. A total of 14 piglets were derived from three sows infected with either or both herpesviruses, yet none tested positive for the viruses indicating that vertical transmission of these viruses is inefficient. Conclusions: The data presented demonstrate that procedures in place are highly sensitive and can specifically detect nucleic acids from target organisms in the panel, thus ensuring the safety of organs for transplantation as well as the monitoring of patients potentially receiving them.